BMI resin formulation for carbon fiber reinforced composite materials, BMI prepreg and carbon fiber reinforced composite materials
By introducing two particles of different particle sizes into the carbon fiber reinforced composite material, the problem of insufficient crack toughness at high temperatures is solved, and the compressive resistance and mechanical properties after impact are significantly improved.
Patent Information
- Application Number
- JP2023558299
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-04
- Filing Date
- 2021-12-02
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-12-02
AI Technical Summary
The existing BMI resins have insufficient crack toughness in carbon fiber reinforced composite materials, especially at high temperatures, which are difficult to meet the needs of high-temperature compressive strength and compressive resistance after impact.
Particles containing two different particle sizes are used as the middle layer material. The first particle (D1) has a particle size pattern of 3-6 microns, accounting for 3-12% of the total resin component, and the second particle (D2) has a particle size pattern of 20-60 microns, accounting for 1-6% of the total resin component.
Remarkably improves post-impact compressive resistance (CAI) and maintains the mechanical and thermal properties of the material at high temperatures, achieving higher crack toughness and compressive strength.
Smart Images

Figure 0007654820000006 
Figure 0007654820000007 
Figure 0007654820000008
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Application No. 63 / 121,632, filed December 4, 2020, entitled "BMI Resin Formulations for Carbon Fiber Reinforced Composites, BMI Prepregs and Carbon Fiber Reinforced Composites," which is incorporated herein by reference.
[0002] The present invention relates to a fiber reinforced prepreg for producing fiber reinforced composite parts suitable for applications requiring high temperature resistance and excellent compressive strength after impact properties. [Background technology]
[0003] A deficiency of current maleimide, bismaleimide (BMI) and benzoxazine (BOX) resins for carbon fiber reinforced composite matrices is the reduction in fracture toughness as measured by Compression After Impact (CAI) of the composite parts. Techniques to increase fracture toughness, such as dissolving thermoplastics in the matrix resin, are not very effective because only a few thermoplastics dissolve in the BMI resin matrix. For example, typical polyimides (PIs) tend to have very high molecular weights, so only small amounts can be dissolved in the BMI resin without causing an undesirable increase in viscosity at room temperature. This high viscosity reduces the tack of the prepreg, resulting in a brittle prepreg. Other low molecular weight thermoplastics, such as amine-terminated polyethersulfone (PES), require high loadings in the thermoset resin composition to affect the toughness of the BMI or BOX matrix. Such large amounts of PES begin to degrade the overall properties of the BMI or BOX matrix, such that the resulting prepreg or composite structure does not have the desirable mechanical and thermal advantages known from BMI and benzoxazine resins.
[0004] Another method that has been attempted to increase the toughness of carbon fiber composites is to apply particles to the interlayer between the plies of prepreg. Traditional particulate interlayer tougheners, such as polyamides, cannot withstand the high service temperatures of BOX and BMI, let alone the higher required cure temperatures. Currently, particles with Tg above 200°C can be used to increase toughness, but are only marginally effective due to their low toughness. They are also poorly soluble in solvents, making it difficult to produce highly spherical particles, which are normally advantageous for good toughening particles. The particles are irregularly shaped because they can only be made small enough by grinding methods, thus further reducing their effectiveness for increasing the toughness of high temperature matrix materials, such as BMI, polyimide, BOX, and certain high temperature epoxies.
[0005] PI particles have traditionally been used to toughen BMI Carbon Fiber Reinforced Prepreg (CFRP) systems. The large amounts of PI particles required to increase toughness have reduced the general use of the material due to economic and mechanical property issues. If the volume of particles incorporated into the prepregs is large, the handleability and tack of those prepregs are compromised, making them difficult to process into parts. Furthermore, if the particle volume is too large, it is difficult to improve the flow properties of the resin system in the prepreg.
[0006] The present inventors have intensively investigated the above problems and have found that the above problems can be solved by preparing a fiber reinforced prepreg incorporating a bismaleimide or BOX resin composition as a matrix and interlaminar particles that include particles of two different sizes. Summary of the Invention
[0007] A fiber reinforced prepreg comprising reinforcing fibers and a thermosetting resin composition. The thermosetting resin composition comprises, consists of, or consists essentially of a first comonomer (A), a second comonomer (B), and particles (D). The particles (D) are insoluble in the first comonomer (A) and the second comonomer (B). The particles (D) comprise, consist of, or consist essentially of 4-18% by volume of the total thermosetting resin composition in the prepreg, and have a particle size in the range of 1-100 microns, and at least one mode of 3-60 microns, on a volume basis. A cured composite made from a fiber reinforced prepreg has a mechanical strength, measured according to ASTM standard ASTM D7137M-17, after impact with 4.45 kJ / m, as described in detail in the examples herein, when at least one of the following conditions i) or ii) is met: 241MPa It has a compressive strength after impact (CAI) of 100% or more.
[0008] i) the first comonomer (A) comprises, consists of, or consists essentially of a maleimide compound and the second comonomer (B) comprises, consists of, or consists essentially of at least one of an alkenylphenol group, an alkenylphenoxy group, or a diamine group; or ii) Particles (D) include, consist of, or consist essentially of particles (D1) and (D2), particles (D1) comprise, consist of, or consist essentially of 3 to 12 volume% of the total thermosetting resin composition in the prepreg, including 3 to 12 volume% of the total thermosetting resin composition in the prepreg, and have a particle size in the range of 1 to 10 microns and a mode of 3 to 6 microns on a volume basis, particles (D2) comprise, consist of, consist of, consist of 1 to 6 volume% of the total thermosetting resin composition in the prepreg, including 1 to 6 volume% of the total thermosetting resin composition in the prepreg, or consist essentially of 1 to 6 volume% of the total thermosetting resin composition in the prepreg, and have a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis.
[0009] A thermosetting resin composition is also provided. The thermosetting resin composition comprises, consists of, or consists essentially of a first comonomer (A), a second comonomer (B), and particles (D). The particles (D) are insoluble in the first comonomer (A) and the second comonomer (B). The particles (D) comprise, consist of, or consist essentially of 4-18% by volume of the total thermosetting resin composition in the prepreg, and have a particle size in the range of 1-100 microns, and at least one mode of 3-60 microns, on a volume basis. At least one of the following conditions i) or ii) is satisfied:
[0010] i) the first comonomer (A) comprises a maleimide compound and the second comonomer (B) comprises at least one of an alkenylphenol group, an alkenylphenoxy group, or a diamine group; or ii) Particles (D) include particles (D1) and (D2), particles (D1) have a particle size in the range of 1 to 10 microns and a mode of 3 to 6 microns on a volume basis, and particles (D1) comprise 3 to 12 volume% of the entire thermosetting resin composition, particles (D2) have a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and particles (D2) comprise 1 to 6 volume% of the entire thermosetting resin composition.
[0011] Additionally, a method for making a thermosetting resin composition is provided, the method comprising the steps of: a first comonomer (A), a second comonomer (B), Particles (D1) and comprising, consisting of, or consisting essentially of a step of merging particles (D2) and
[0012] The particles (D1) and the particles (D2) are insoluble in the first comonomer (A) and the second comonomer (B). The particles (D1) have a particle size in the range of 1 to 10 microns and a mode of 3 to 6 microns on a volume basis, and the particles (D1) comprise 3 to 12 volume % of the entire thermosetting resin composition. The particles (D2) have a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and the particles (D2) comprise 1 to 6 volume % of the entire thermosetting resin composition.
[0013] Cured composites made from these fiber reinforced prepregs exhibit excellent compression after impact, as well as other desirable properties as described herein. [Brief description of the drawings]
[0014] [Figure 1] 1 shows an example of a typical frequency distribution of particles (D1) and (D2) plotted as a function of volume percentage of particle size. [Diagram 2] The effect of varying two different particle size levels on CAI is shown. [Diagram 3]FIG. 2 shows a cross-sectional view of a cured laminate showing a fibrous layer and an intermediate layer containing particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present inventors have found that the inclusion of a population of particles (D) in a resin composition comprising a first comonomer (A) and a second comonomer (B) improves the CAI of a cured fiber reinforced composite (FRC) part. The population of particles (D) is insoluble in the first comonomer (A) and the second comonomer (B), the particles (D) comprise, consist of, or consist essentially of 4-18% by volume of the total thermosetting resin composition in the prepreg, and have a particle size in the range of 1-100 microns, and at least one mode of 3-60 microns, on a volume basis. To achieve an improvement in the CAI of the cured composite, at least one of the following two conditions is met. These conditions are: i) comonomer (A) comprises, consists of, or consists essentially of a maleimide compound and a second comonomer (B) comprises, consists of, or consists essentially of at least one alkenylphenol group, or alkenylphenoxy group, or diamine group.
[0016] ii) Particles (D) comprise, consist of, or consist essentially of two particle populations (D1) and (D2). Each particle population (D1) and (D2) has its own particle size range and its own mode, by volume, within each corresponding distribution. Particles (D1) have a particle size in the range of 1-10 microns and a mode, by volume, of 3-6 microns. Particles (D1) comprise 3-12% by volume of the total thermosetting resin composition, and particles (D2) have a particle size in the range of 10-100 microns and a mode, by volume, of 20-60 microns, and particles (D2) comprise 1-6% by volume of the total thermosetting resin composition.
[0017] The CAI values referred to herein are measured using cured fiber-reinforced composites made and cured according to the procedure using carbon fibers as described in the Examples, and the measurement is performed according to standard ASTM D 7137M-17 after impact at 4.45 kJ / m.
[0018] As used herein, mode is the most prevalent particle size within each range of particle sizes on a volume basis. As used herein, the terms volume percentage of the total thermosetting resin composition or volume % of the total thermosetting resin composition refer to the volume % including the thermosetting resin and any other additives, including particles (D), which may include particles (D1) and (D2), but not including the fibers in the prepreg or composite.
[0019] The matrix of these prepregs is a thermosetting resin composition. According to one embodiment, the thermosetting composition may include a first comonomer (A) that includes, consists of, or consists essentially of a maleimide or bismaleimide compound, and a second comonomer (B). According to certain embodiments, the maleimide compound of the first comonomer (A) may include at least one of N,N'-4,4'-diphenylmethane-bismaleimide, N,N'-2,4-toluene-bismaleimide, N,N'-2,2,4-trimethylhexane-bismaleimide, or mixtures thereof. According to certain embodiments, the first comonomer maleimide compound (A) may be a eutectic mixture of two or more bismaleimide compounds. As used herein, the term "eutectic" means that the melting point of the mixture is the lowest and is lower than the melting points of the individual bismaleimide compounds. The comonomer (B) may include at least one of an alkenylphenol group, an alkenylphenoxy group, or a diamine group. According to a particular embodiment, the comonomer (B) may be o,o'-diallylbisphenol A.
[0020] Particles (D), which may include, consist of, or consist essentially of particles (D1) and particles (D2), are insoluble in the first comonomer (A) and the second comonomer (B). Particles (D) may include, consist of, or consist essentially of 4-18% by volume of the total thermosetting resin composition in the prepreg, and have a particle size in the range of 1-100 microns, and at least one mode of 3-60 microns, on a volume basis. Particles (D1) may be present in the prepreg at 3-12% by volume of the total thermosetting resin composition in the prepreg. Particles (D1) may have a particle size in the range of 1-10 microns, and a mode of 3-6 microns, on a volume basis. The particles (D2) may be present in the prepreg at 1 to 6% by volume of the total thermosetting resin composition in the prepreg. The particles (D2) may have a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis. According to another embodiment, the particles (D2) may have a particle size in the range of 20 to 60 microns and a mode of 20 to 50 microns on a volume basis.
[0021] As mentioned above, the fiber reinforced prepreg may have at least two layers, called the fiber layer and the intermediate layer. The fiber layer comprises reinforcing fibers impregnated with a thermosetting resin composition of maleimide component (A) and comonomer (B), but in one embodiment, the fiber layer preferably does not contain or contains almost no particles (D), which may include particles (D1) and particles (D2). The intermediate layer comprises a thermosetting resin composition and particles (D), which may include particles (D1) and (D2), but does not contain (or contains almost no) reinforcing fibers, as is known in the art. In one embodiment, at least 90% by volume of the total amount of particles (D), which may include particles (D1) and particles (D2), remains in the intermediate layer after curing of the prepreg.
[0022] In one embodiment, particles (D) comprise polyimide particles. In one embodiment, particles (D1) comprise polyimide particles. In one embodiment, particles (D2) comprise polyimide particles. According to one embodiment, particles (D) may have a glass transition temperature of 200° C. or higher. In yet another embodiment, particles (D) may have a glass transition temperature of 220° C. or higher. According to one embodiment, particles (D1) may have a glass transition temperature of 200° C. or higher. In yet another embodiment, particles (D1) may have a glass transition temperature of 220° C. or higher. In one embodiment, particles (D2) may have a glass transition temperature of 200° C. or higher. In yet another embodiment, particles (D1) may have a glass transition temperature of 220° C. or higher.
[0023] According to one embodiment, the thermosetting resin composition may further include a thermoplastic material (C) dissolved therein. Particles (D), which may include particles (D1) and particles (D2), are not dissolved in the thermoplastic material (C). In one embodiment, the thermoplastic material (C) may be a polyimide and may be present in an amount of 0.5 to 5% by weight of the total thermosetting resin composition, excluding particles (D), which may include particles (D1) and (D2).
[0024] The thermosetting resin composition may further include an accelerator, also referred to herein as a catalyst, in an amount sufficient to reduce the resin flow index of the thermosetting resin composition at 40° C. to 5 or less. According to one embodiment, the amount of accelerator may be 0.05-0.5% by weight based on components (A) and (B). In another embodiment, the accelerator may be a phosphorus-containing accelerator. The thermoplastic (C) helps reduce the tack of the prepreg, affecting its handling properties. However, the presence of the thermoplastic reduces the viscosity of the thermosetting resin composition before it is fully cured during curing. This can cause the thermosetting resin to move and flow unnecessarily during curing. Thus, the accelerator helps to increase the cure rate of the thermosetting resin composition, increasing its viscosity and reducing unwanted flow and movement of the thermosetting resin during the curing cycle.
[0025] The present invention further provides a fiber reinforced composite article or fiber reinforced composite part or fiber reinforced composite material obtained by curing the fiber reinforced prepreg disclosed herein. Further, a method for producing a fiber reinforced composite material or fiber reinforced composite article or fiber reinforced composite part is provided, which is a method for curing a fiber reinforced prepreg at a temperature of 180°C to 300°C. The present invention further provides a thermosetting resin composition. The thermosetting resin composition comprises a first comonomer (A), a second comonomer (B), and particles (D), consists of a first comonomer (A), a second comonomer (B), and particles (D), or consists essentially of a first comonomer (A), a second comonomer (B), and particles (D). The particles (D) are insoluble in the first comonomer (A) and the second comonomer (B), the particles (D) comprise 4 to 18 volume % of the total thermosetting resin composition in the prepreg, and have a particle size in the range of 1 to 100 microns and at least one mode of 3 to 60 microns on a volume basis. At least one or both of the following conditions i) or ii) are satisfied.
[0026] i) the first comonomer (A) comprises, consists of, or consists essentially of a maleimide compound, and the second comonomer (B) comprises, consists of, or consists essentially of at least one alkenylphenol group, or an alkenylphenoxy group, or a diamine group.
[0027] ii) Particles (D) comprise particles (D1) and (D2), consist of particles (D1) and (D2), or consist essentially of particles (D1) and (D2), particles (D1) having a particle size in the range of 1 to 10 microns and a mode of 3 to 6 microns on a volume basis, and particles (D1) comprising 3 to 12 volume % of the total thermosetting resin composition, particles (D2) having a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and particles (D2) comprising 1 to 6 volume % of the total thermosetting resin composition.
[0028] A fiber reinforced prepreg may have fiber layers and an intermediate layer. The intermediate layer is a layer of resin between the fiber layers and contains particles (D), which may include particles (D1) and (D2) as shown in FIG. 3. As known in the art, an intralayer of resin is the resin between the fibers in the fiber layers. Fiber reinforced prepregs may be manufactured by one of two methods.
[0029] In the first method, a prepreg can be formed by impregnating one or both sides of a fiber layer, such as a fiber tow, mesh, fabric, or bundle, with a single film containing particles (D), which can include a thermosetting resin composition, particles (D1) and particles (D2). In this method, the fibers can help to "filter" the particles (D) during the impregnation process so that they do not penetrate into the layer of resin between the fibers of the fiber layer. Thus, according to this method, after impregnation and curing, 90% or more by volume of the total particles (D) remains in the middle layer rather than being in the layer of the fiber layer.
[0030] In the second method, a prepreg may be formed by first impregnating one or both sides of a fiber layer, such as a fiber tow, mesh, fabric, or bundle, with a first layer of resin film containing a thermosetting resin composition but not particles (D). The next step in this second method is to place a second layer of resin film containing a thermosetting resin and particles (D), which may include particles (D1) and (D2), on one or both sides of the first layer of resin film. Thus, in certain embodiments, an intermediate layer may be formed by placing a thermosetting resin containing particles (D) on a fiber layer such that 90% or more by volume of the total particles (D), which may include particles (D1) and (D2), remains in the intermediate layer after curing. That is, after curing, 10% or less by volume of particles (D) resides in the layer between the fibers in the fiber layer.
[0031] Fiber-reinforced prepregs, as cured composites, are 241MPa The prepreg may have a Compression After Impact (CAI) value of 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or more by volume of particles (D) remaining in the intermediate layer after curing of the prepreg. The particles (D) comprise 4 to 18% by volume of the total thermosetting resin composition in the prepreg and have a particle size in the range of 1 to 100 microns and at least one mode of 3 to 60 microns on a volume basis. According to a specific embodiment, the CAI of the cured prepreg is 241 , 259 , 276 , 293 , 310 , 328 ,or 345MPa It could be more than that.
[0032] A CAI of 35 ksi or more can be achieved by the inclusion of particles (D) including, consisting of, or consisting essentially of particles (D1) and (D2), particles (D1) having a particle size in the range of 1 to 10 microns and a mode of 3 to 6 microns on a volume basis, and particles (D1) comprising 3 to 12 volume % of the total thermosetting resin composition, particles (D2) having a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and particles (D2) comprising 1 to 6 volume % of the total thermosetting resin composition including a first comonomer (A) and a second comonomer (B). In this embodiment, the first and second comonomers are not particularly limited.
[0033] According to another embodiment, the fiber reinforced prepreg, as a cured composite, comprises: 241 , 259 , 276 , 293 , 310 , 328 ,or 345MPa or more. In this embodiment, the particles (D) comprise 4-18% by volume of the total thermosetting resin composition in the prepreg, and have a particle size in the range of 1-100 microns, and at least one mode of 3-60 microns on a volume basis, the first comonomer (A) comprises a maleimide compound, and the second comonomer (B) comprises at least one of an alkenylphenol group, an alkenylphenoxy group, or a diamine group. According to another embodiment, the comonomer (B) may comprise a vinyl group.
[0034] According to another embodiment, the thermosetting resin composition in the fiber reinforced prepreg further comprises a thermoplastic material (C).
[0035] Particles (D) may include one or more types of particles. For example, particles (D) may be a blend of different size populations (D1) and (D2). Particles (D) may be a blend of particles made from different materials. Particles (D1) may include particles made from one or more materials. Particles (D2) may include particles made from one or more materials. The volume ratio of small particles (D1) to large particles (D2) may be 90:10 to 50:50, or 90:10 to 60:40, or 80:20 to 60:40. The volume ratio of (D1) to (D2) may be 90:10, or 80:10, or 70:30, or equal to or greater than 60:40, or equal to or greater than 50:50.
[0036] The fiber reinforced prepreg may have a fiber layer and an intermediate layer. To prepare the fiber layer, a thermosetting resin composition that does not contain particles (D) (or contains 10 volume % or less) may be impregnated into a fiber layer containing reinforcing fibers. To prepare the intermediate layer, a thermosetting resin composition that contains particles (D) may be disposed on the fiber layer. In one embodiment, 90% or more of the particles (D) may remain in the intermediate layer after curing, based on the total volume of the particles (D).
[0037] The fiber-reinforced prepreg containing the thermosetting resin composition has the following properties after curing: 241MPa According to a particular embodiment, the CAI may include: 241 , 259 , 276 , 293 , 310 , 328 ,or 345MPa Some embodiments of the present invention allow for the use of smaller amounts (by volume) of particles when toughness is not specifically required for CFRP. 241MPa The reduction in the amount of particles by volume may further enhance other properties, such as compressive strength and compressive type properties such as Open Hole Compression (OHC). According to certain embodiments of the present invention, the fiber reinforced prepreg, or cured composite made with the thermosetting resin composition, may have a CAI of greater than 100%. 345MPaThis property has a significant impact in applications where toughness is important for CFRP parts such as those requiring high impact resistance (e.g., for primary structures in aerospace parts).
[0038] In a specific exemplary embodiment, a cured BMI matrix resin obtained by curing the BMI resin is provided. In addition, according to a specific embodiment, a prepreg is provided by impregnating a reinforcing fiber with the thermosetting resin composition and particles (D) that may include particles (D1) and (D2) such that 90% by volume or more of the particles (D) remain in the intermediate layer of the prepreg after curing. In addition, a fiber-reinforced composite material, fiber-reinforced composite part, or fiber-reinforced composite product is provided, which includes a cured product obtained by curing a prepreg including the BMI resin composition and a reinforcing fiber base material, in which 90% by volume or more of the particles (D) (which may include particles (D1) and (D2)) are contained in the intermediate layer. When 90% by volume or more of the particles (D) are contained in the intermediate layer after curing, the particles (D) can effectively increase the toughness of the cured CFRP. Particle (D) and particles (D1) and (D2) The present inventors have found that the inclusion of particles (D) having a specific size range in the intermediate layer between the plies of the fiber reinforced prepreg from which the cured part is made improves the CAI of the cured fiber reinforced composite (FRC) part. In particular, when the first comonomer (A) comprises a maleimide compound and the second comonomer (B) comprises at least one of an alkenylphenol group, an alkenylphenoxy group, or a diamine group, particles (D) comprising 4-18% by volume of the total thermosetting resin composition in the prepreg, having a particle size in the range of 1-100 microns, and at least one mode of 3-60 microns on a volume basis, have a particle size of 4-18% by volume of the total thermosetting resin composition in the prepreg, measured according to ASTM standard ASTM D7137M-17 by the procedure described in the examples of this specification after impact at 4.45 kJ / m. 241MPaIt is effective to provide a cured composite having a CAI of equal to or greater than 100 microns. (D) Particles may have a particle size ranging from 1 to 100 microns, 10 to 90 microns, 10 to 80 microns, 20 to 100 microns, 10 to 70 microns, 30 to 100 microns, 5 to 95 microns, 10 to 95 microns, 3 to 85 microns, 4 to 60 microns, 1 to 70 microns, or 3 to 85 microns. At least one mode of particles (D) may be 3 to 60 microns, 5 to 55 microns, 10 to 50 microns, or 15 to 45 microns.
[0039] According to some embodiments, particles (D) may comprise, consist of, or consist essentially of at least two particle populations, referred to herein as (D1) and (D2).
[0040] The inventors have found that the CAI of cured fiber reinforced composites (FRCs) is improved when at least two sizes of particles, referred to herein as particles (D1) and particles (D2), are included in the interlayer between the plies of fiber reinforced prepregs from which the cured parts are made. Thus, the interlayers of these prepregs contain these two particle populations (D1) and (D2). Each particle population (D1) and (D2) has its own particle size range and mode, on a volume basis. As used herein, the mode is the most prevalent particle size within each range of particle sizes, plotted as a frequency distribution by volume. Figure 1 shows an example of a frequency distribution showing the mode and diameter range by volume percentage for particles (D1) and (D2). The mode for each of particles (D1) and (D2) is the most frequent diameter by volume (i.e., the peak) within each range of particle sizes. Figure 1 shows multiple plots with different volume ratios of small particles (D1) to large particles (D2). As seen in FIG. 1, the mode of the (D1) particle is the modal volume in the diameter range of 1 micron to approximately 10 microns. The mode of the large particle (D2) is the modal diameter by volume (i.e., peak) in the diameter range of approximately 10 microns to approximately 100 microns. The lower limit of the diameter range of the particle (D1) is defined as the first diameter with a non-zero volume frequency. The upper limit of the diameter range of the particle (D1) is either the first largest diameter with a non-zero volume frequency after the (D1) mode diameter, or the first smallest volume frequency diameter after the (D1) mode peak that has a diameter larger than the (D1) particle mode. The lower limit of the diameter range of the large particle (D2) is the smallest diameter with a non-zero volume frequency that is the same diameter or larger than the upper limit of the diameter range of the particle (D1). Thus, the upper limit of the diameter range of the (D1) diameter can be the same as the lower limit of the diameter range of the particle (D2). The upper limit of the diameter range of a (D2) particle is the last non-zero volume frequency diameter having a diameter larger than the mode of the (D2) particle.
[0041] After extensive research, the inventors have surprisingly found that when these two distinct (populations) of particle size ranges and modes are present together in the interlayer, the toughness of the cured BMI CFRP can be enhanced such that a smaller total amount of particles may be required than if only a single mode size range of particles is utilized. Particles (D1) may have a particle size ranging from 1 to 15 microns, and a mode of particle size, by volume, of 4 to 6 microns. The amount of particles (D1) in the total resin system may be 3 to 12 volume % of the total thermosetting resin composition. The amount of particles (D1) may be 1 to 15 volume %, or 2 to 13 volume %, or 4 to 10 volume %, or 5 to 15 volume %, or 1 to 20 volume %, or 3 to 15 volume %, or 5 to 10 volume % of the total thermosetting resin composition. Particles (D2) contain particles having a diameter size ranging from 15 to 100 microns. The amount of (D2) particles in the total resin system can be 1-6% by volume, or 1-13% by volume, or 0.1-10% by volume, or 1-7% by volume, or 2-10% by volume, or 3-8% by volume, or 2-5% by volume, or 0.5-4% by volume, of the total thermosetting resin composition. Without wishing to be bound by any theory, when the diameter of the particles (D1) ranges from more than 1 micron to less than 10 microns, the particles (D1) can effectively increase the loading level of the (D1) particles in the intermediate layer, thereby increasing the toughness of the CFRP and increasing the CAI of the CFRP. When the particles (D2) have a diameter range between 10-100 microns or 15-130 microns, without wishing to be bound by any theory, the particles (D2) can effectively create an intermediate layer having a sufficient thickness to increase the concentration of the particles (D1) in the intermediate layer, thereby effectively increasing the toughness of the CFRP. When the amount of particles (D1) is 3 to 12 volume % of the total thermosetting resin composition, and the amount of particles (D2) is 1 to 6 volume % of the total thermosetting resin composition, the CAI can be increased to a higher level than when each particle size group (D1) or (D2) is used alone with the same total volume of particles present.For example, the volume percent of the particles (D1) relative to the entire thermosetting resin composition may be 1 to 45 volume percent, 10 to 40 volume percent, 15 to 35 volume percent, 20 to 30 volume percent, 4 to 12 volume percent, 1 to 20 volume percent, 5 to 15 volume percent, or 3 to 10 volume percent of the entire thermosetting resin composition. The volume percent of the particles (D2) relative to the entire thermosetting resin composition may be 0.5 to 6 volume percent, 1 to 6 volume percent, 1 to 7 volume percent, 1 to 10 volume percent, 1 to 15 volume percent, 2 to 14 volume percent, 3 to 13 volume percent, 1.5 to 10 volume percent, 5 to 13 volume percent, or 5 to 10 volume percent.
[0042] The diameter range of the particles (D1) can be 1-15 microns, or 1-14 microns, or 1-13 microns, or 2-12 microns, or 1-10 microns. The mode by volume of the particles (D1) can fall anywhere within these ranges. The mode by volume of the particles (D1) can be 1-15 microns, or 1-14 microns, or 1-13 microns, or 2-12 microns, or 1-10 microns, or 3-7 microns, or 4-6 microns, or 2-10 microns, or 3-6 microns. Without wishing to be bound by a particular theory, when the (D1) particles are within these ranges, the (D1) particles can create sufficiently close packing between the (D2) particles to impart toughness. Particles larger than 1 micron can penetrate to the interlayer. Particles smaller than 15 microns can increase the packing density, which can increase the toughness of the cured CFRP component.
[0043] The diameter range of the particles (D2) can be 10-200 microns, or 10-100 microns, or 10-90 microns, or 10-70 microns, or 10-60 microns, or 11-150 microns, or 12-120 microns, or 13-150 microns, or 14-140 microns, or 10-120 microns, or 15-145 microns. The volume mode of the particles (D2) can fall anywhere within those aforementioned ranges. The volume mode of the particles (D2) can be 10-100 microns, or 20-80 microns, or 40-60 microns, or 10-200 microns, or 11-150 microns, or 12-120 microns, or 13-150 microns, or 14-140 microns, or 10-120 microns, or 15-145 microns, or 20-60 microns, or 15-70 microns, or 30-50 microns. Without wishing to be bound by a particular theory, it is believed that if the (D2) particles are within this size range, the (D2) particles will produce sufficient interlayer thickness to allow the use of fewer (D1) particles. This size range may produce a thicker interlayer while using fewer (D1) particles. The lower amount of particles may result in better resin flow, improving the quality of the CFRP part and reducing the possibility of void formation, especially during low pressure curing, e.g., processing outside of an autoclave, or when using fabric structures as prepreg substrates.
[0044] If all of the above conditions are met, the fracture toughness of the cured composite part or cured prepreg, as measured by CAI, may be increased, and the CAI of the cured composite or cured prepreg may be: 276MPaor it may be higher than if the two different particle sizes (D1) and (D2) were not included in the prepreg. By incorporating only the particles (D1) containing the small particle size, a lower total amount (volume) of particles (D1) and (D2) can be used, although a similar CAI result can be achieved by adding only the small particles at a high loading (volume) when both particles (D1) and particles (D2) are present. It is effective in making the material easier to handle, for example, increasing tack and flexibility. Furthermore, the reduction in the amount of particles in the system allows the resin flow to be controlled by adding both the dissolved thermoplastic and the accelerator in controlled amounts, in order to control the tack and resin flow independently of each other.
[0045] Without being bound by any particular theory, it is believed that when the particles (D1) are small enough, they can better fill the void volume between the large particles (D2), so that the large particles (D2) can maintain a sufficient thickness for the interlayer. Small particles (D1) may be more efficient in increasing toughness, but would not be able to maintain a sufficient interlayer thickness to effectively increase the fracture toughness of the carbon fiber reinforced plastic (CFRP). By incorporating a small amount of large particles (D2), the interlayer thickness can be maintained, so that the fracture toughness of the CFRP increases while having a large volume of small particles (D1) (compared to the amount of large particles (D2)). Furthermore, for high Tg matrix materials, the volume ratio of (D1) to (D2) is important because the viscosity of these resin matrix systems upon curing is very low. Due to this low viscosity, it is very difficult to maintain the interlayer thickness, and it has been found that keeping the particles (D1) and (D2) within a certain relative amount range between the large particles (D2) and the small particles (D1) increases the effectiveness of the small particles (D1) while the interlayer thickness can be maintained to improve fracture toughness. This further helps improve the robustness of the cured CFRP properties, allowing for different cure cycles and bagging configurations without having to adhere to very strict curing and bagging schedules that limit the use of other similar materials. Additionally, the reduced volumetric amount of particles in the matrix system allows for greater flexibility in the amount of thermoplastic and accelerators used to control the flow and tack of the matrix system.
[0046] Furthermore, a certain minimum volume threshold of large particles may be effective to maintain interlayer thickness, and above this threshold, the addition of additional (D2) particles would not be necessary to significantly improve the CAI of the cured composite part. If the particle content of (D2) particles is kept below 6%, the prepreg handling is good and resin flow is sufficient to result in a fully consolidated and cured CFRP panel with reduced or no voids. This is particularly advantageous when producing prepregs using fabrics where resin flow is important to fill the free volume upon curing, reducing void content. An additional benefit of keeping the particle content low is tack control. With low particle content, tack can be controlled using different amounts of melted thermoplastic. This can be particularly important for customizing the tack of the prepreg, which is an important property of the prepreg. Figure 2 shows an example plot of the CAI of cured composites with no particles (D2), 2 vol.% particles (D2), and 3 vol.% particles (D2). As can be seen from Figure 2, increasing the volume percentage of small particles (D1) also increases the CAI of the cured composite. However, a higher amount of particles (D2), 3 vol%, has a lower CAI than a composite made with 2 vol% of large particles (D2) at the same loading of small particles (D1). Similarly, it can be seen that approximately 7 vol% to 18 vol% of particles (D1), without any (D2) particles, results in a lower CAI than cured composites made with approximately 4 vol%, 5 vol%, or 6 vol% of (D1) particles, further containing either 2 vol% or 3 vol% of (D2) particles.
[0047] According to certain embodiments of the present invention, when (D1) particles and (D2) particles are combined, the combination may have a particle size distribution similar to that of FIG. 2, which has two distinct modes. In other embodiments, the combination may have only one mode. In still other embodiments, where the (D1) particle size distribution has one or more modes and the (D2) particle size distribution has one or more modes, when the particle size distribution is measured, the combined particle size distribution of the (D1) particles and the (D2) particles may have a particle size distribution with two or more modes. This combination of particle sizes may have different particle size distributions, for example, asymmetric distributions with different values for the mean, median, and mode. The particle size distribution may have at least two or more modes, such that the (D1) particles are the major mode, and the minor mode may consist of both the (D1) particles and the (D2) particles.
[0048] When the particles are combined, the particle size range at half height may be between 2 microns and 80 microns, in other embodiments the particle range may be between 3 microns and 60 microns at half height on the particle distribution plot, and the distribution may have one or more modes.
[0049] In certain embodiments, the particles (D1) and (D2) may each have a Tg greater than 200°C. Since the matrix system used has a Tg greater than 200°C, the incorporation of particles with a Tg less than 200°C would significantly reduce the mechanical properties of the CFRP, especially at high temperatures and under water-saturated conditions. In other embodiments, the particles will have a Tg greater than 220°C. The incorporation of particles with a Tg greater than 220°C greatly increases the thermo-oxidative stability of the matrix resin system and ultimately of the cured CFRP. The particles (D1) and / or particles (D2) with a Tg greater than 220°C may further reduce the impact on the ultimate Tg of the cured thermosetting resin material. This is particularly important in the case of matrices such as BMI or BOX, and certain high Tg epoxies whose cured Tg may be greater than 220°C. For example, the glass transition temperature of the particles (D1) or (D2) may be from 200° C. to 1500° C., or from 220° C. to 1500° C. or higher.
[0050] The particles (D1) and (D2) may be formed from the same material or different materials. The particles (D1) and (D2) may each be a mixture of various materials. The particles (D1) and / or (D2) that may be incorporated into the aforementioned embodiment of the resin system may be selected from polyimide (PI), polyetherimide (PEI), polyamideimide (PAI), and mixtures thereof. The thermoplastic toughener particles (D1) and / or (D2) may be any of the thermoplastic polyimide particles described in U.S. Pat. Nos. 5,248,711 and 5,120,823, the disclosures of which are incorporated herein by reference in their entirety for all purposes. The particles (D1) and / or (D2) may be formed by the reaction between a dianhydride and a diamine. The particles (D1) and / or (D2) may be formed by crushing or grinding polyimide or other thermoplastic materials under cryogenic conditions. The particles (D1) and / or (D2) can also be formed by suspension precipitation.
[0051] Suitable exemplary commercially available toughener particles (D1) and / or (D2) include high performance powder P84 available from Evonik Industries AG. P84 powder is made according to the teachings of U.S. Pat. No. 4,001,186, the entire contents of which are incorporated herein by reference for all purposes. P84 powder is a polyimide of benzophenone tetracarboxylic anhydride (BTDA), toluene diamine, and 4,4′-diaminodiphenylmethane. Other exemplary thermoplastic tougheners include polyetherimides such as ULTEM® 1000 available from Sabic, Al-Jubail, Saudi Arabia. High performance powder P84 powder may be the preferred thermoplastic toughener since it has the highest Tg of these options. Thermoplastic tougheners are added in an amount that provides the desired degree of toughening of the prepreg resin consistent with the performance requirements of each application.
[0052] In certain embodiments, the large particles (D2) may be composed of certain inorganic materials. For example, the (D2) particles may be comprised of, may consist of, or may essentially consist of any type of inorganic particles, such as clay. Examples of suitable inorganic particles for (D2) include metal oxide particles, metal particles, and mineral particles. Examples of other suitable inorganic materials for the particles (D2) include aluminum hydroxide, magnesium hydroxide, glass beads, glass flakes, and glass balloons (i.e., hollow glass particles).
[0053] Examples of other materials suitable for particles (D2) include particulate metal oxides such as silicon oxide, titanium oxide, zirconium oxide, zinc oxide, tin oxide, indium oxide, aluminum oxide, antimony oxide, cerium oxide, magnesium oxide, iron oxide, tin-doped indium oxide (ITO), antimony-doped tin oxide, and fluorine-doped tin oxide. Examples of particulate metals suitable for (D2) particles include gold, silver, copper, titanium, aluminum, nickel, iron, zinc, and stainless steel. Examples of minerals suitable for particles (D2) include montmorillonite, talc, mica, boehmite, kaolin, smectite, xonotlite, vermiculite, and sericite.
[0054] Examples of carbonaceous materials suitable for the particles (D2) include carbon black, acetylene black, ketjen black, carbon nanotubes, graphene, carbon nanofibers, carbon nanobeads, fullerenes, and the like. First Comonomer (A) Maleimide Compound (A) The first comonomer (A) is not particularly limited, but according to certain embodiments, may comprise, consist of, or consist essentially of at least one maleimide compound.
[0055] The maleimide or bismaleimide compound containing the first comonomer (A) in the present invention may include any of the known bismaleimide compounds. The terms "maleimide" and "bismaleimide" are used interchangeably herein. The bismaleimide compound of the first comonomer (A) is typically prepared by reacting maleic anhydride or substituted maleic anhydride with aromatic and / or aliphatic diamines. Exemplary bismaleimides are as follows: N,N'-4,4'-diphenylmethane-bismaleimide, N,N'-2,4-toluene-bismaleimide, N,N'-2,6-toluene-bismaleimide, N,N'-2,2,4-trimethylhexane-bismaleimide, N,N'-ethylene-bismaleimide, N,N'-ethylene-bis(2-methyl)maleimide, N,N'-trimethylene-bismaleimide, N,N'-tetramethylene-bismaleimide, N,N'-hexa Methylene-bismaleimide, N,N'-1,4-cyclohexylene-bismaleimide, N,N'-meta-phenylene-bismaleimide, N,N'-para-phenylene-bismaleimide, N,N'-4,4'-3,3'-dichlorodiphenylmethane-bismaleimide, N,N'-4,4'-diphenylether-bismaleimide, N,N'-4,4'-diphenylsulfone-bismaleimide, N,N'-4.4'-dicyclohexyl N,N'-α,α'-4.4'-dimethylenecyclohexane-bismaleimide, N,N'-meta-xylene-bismaleimide, N,N'-para-xylene-bismaleimide, N,N'-4,4'-diphenylcyclohexane-bismaleimide, N,N'-metaphenylene-bistetrahydrophthalimide, N,N'-4,4'-diphenylmethanebiscitraconimide, N,N'-4,4'-2,2-di Phenylpropane-bismaleimide, N,N'-4,4-1,1-diphenylpropane-bismaleimide, N,N'-4,4'-triphenylmethane-bismaleimide, N,N'-α,α'-1,3-dipropylene-5,5-dimethylhydantoin-bismaleimide, N,N'-4,4'-(1,1,1-triphenylethane)-bismaleimide, N,N'-3,5-triazole-1,2,4-bismaleimide, N,N'-4,4'-Diphenylmethane bis-itaconimide, N,N'-para-phenylene bis-itaconimide, N,N'-4,4'-diphenylmethane bisdimethylmaleimide, N,N'-4,4'-2,2-diphenylpropane bisdimethylmaleimide, N,N'-hexamethylene bisdimethylmaleimide, N,N'-4,4'-(diphenylether) bisdimethylmaleimide, N,N'-4,4'-diphenylsulfone bisdimethylmaleimide N,N'-(oxydi-para-phenylene)bismaleimide, N,N'-(oxydi-para-phenylene)-bis-(2-methylmaleimide), N,N'-(methylenedi-para-phenylene)-bismaleimide, N,N'-(methylenedi-para-phenylene)-bis-(2-methylmaleimide), N,N'-(methylenedi-para-phenylene)-bis-(2-phenylmaleimide), N,N'-(sulfonyldi-para-phenylene)-bismaleimide, N,N '-(Thiodi-para-phenylene)-bismaleimide, N,N'-(dithiodi-para-phenylene)-bismaleimide;N,N'-(sulfonyldi-meta-phenylene)-bismaleimide, N,N'-(ortho,para-isopropylidenediphenylene)-bismaleimide, N,N'-(isopropylidenedi-para-phenylene)-bismaleimide, N,N'-(ortho,para-cyclohexylidene diphenylene)-bismaleimide, N,N'-(cyclohexylidene diphenylene)-bismaleimide N,N'-(ethylenedi-para-phenylene)-bismaleimide, N,N'-(4,4"-para-triphenylene)-bismaleimide, N,N'-(para-phenylenedioxy-di-para-phenylene)-bismaleimide, N,N'-(methylene-di-para-phenylene)-bis-(2,3-dichloromaleimide), and N,N'-(oxy-di-para-phenylene)-bis-(2-chloromaleimide). The second comonomer (B) The first comonomer (A) and the second comonomer (B) react together to form a thermoset resin.
[0056] The bismaleimide monomers used as the first comonomer (A) described above are rarely used alone, but are usually used as part of a total resin system which may contain other polymerizable species in addition to fillers, rheology control agents, catalysts, fibrous and non-fibrous reinforcing materials, etc. Of particular importance in bismaleimide resin systems are the various comonomers and reactive modifiers used as the second comonomer (B).
[0057] The second comonomers (B) may be interactive in that they react with the bismaleimide, or they may only react with themselves or other system components, and some of these materials may serve more than one function. For example, epoxy resins generally do not react with maleimide groups, but may react with other system components, especially amines, phenols, and anhydrides. In addition, liquid epoxy resins, such as those based on bisphenol A or bisphenol F, can serve as tackifiers, increasing the layup temperature tack of adhesives, matrix resins, and prepregs.
[0058] Among the second comonomers (B) useful together with the maleimides and bismaleimides as the first comonomers (A) are diamines and polyamines, as well as alkenyl and alkenylphenols and phenoxy ethers. Useful diamines and polyamines include, for example, aliphatic amines such as 1,6-diamino-2,2,4-trimethylhexane, 1,6-hexanediamine, 1,8-octanediamine, bis(3-aminopropyl)ether, and the like, as well as aromatic amines such as 1,2-, 1,3-, and 1,4-phenylenediamine, 2,4- and 2,6-toluenediamine, 2,2'-, 2,4'-, 3,3'-, and 4,4'-diaminodiphenylmethane, as well as amines in which the bridging methylene groups are divalent organic groups, such as -CO-, -COO-, -OCOO-, -SO-, -S-, -SO 2and diaminodiphenylmethane analogs substituted with -, -NH-CO-, etc. Prepolymers prepared from bismaleimides and the aforementioned amines are also useful.
[0059] Alkenyl-containing compounds, especially alkenyl aromatic compounds, may also be suitable second comonomers (B). Examples of such compounds include styrene, 1,4-divinylbenzene, terephthalic acid diacrylate, cyanuric acid triacrylate, and glyceryl triacrylate. The corresponding allyl-, methallyl-, methacrylo-, and methylvinyl-containing compounds are also suitable. Useful alkenylphenols and alkenylphenoxy ethers are in particular allylphenol, methallylphenol, and propenylphenol, such as o,o'-diallylbisphenol A, eugenol, eugenol methyl ether, and similar compounds, as disclosed in U.S. Pat. No. 4,100,140. Oligomers terminated with allyl or propenylphenyl groups, or allyl or propenylphenoxy groups, are also useful, such as appropriately terminated polysiloxanes, polyetherketones, polyethersulfones, polyimides, polyetherimides, and the like. Appropriately terminated oligomers may be prepared, for example, by allylation of phenolized dicyclopentadiene followed by rearrangement to allylphenol, as taught in U.S. Pat. No. 4,546,129, incorporated herein by reference. Most preferably, the alkenylphenol is o,o'-diallyl bisphenol A or o,o'-dipropenyl bisphenol A. The alkenylphenol comonomers and alkenylphenoxy comonomers are utilized in amounts up to 70% by weight based on the weight of the total system, in some embodiments from 10 to 50%, and in other embodiments from about 20 to about 40%. When the amount of alkenyl-containing comonomer is greater than 10% in the BMI mixture, it may have a high modulus and high Tg. When it is greater than 30%, it may improve the toughness and handling of the resin.
[0060] Specific examples include o,o'-diallyl bisphenol A, eugenol, eugenol methyl ether, and similar compounds as disclosed in U.S. Patent No. 4,100,140, the entirety of which is incorporated herein by reference. Particularly preferred second comonomers (B) are o,o'-diallyl bisphenol A and o,o'-dipropenyl bisphenol A. Compimide® TM124 is a commercially available co-curing agent available from Evonik Industries AG and contains o,o'-diallyl bisphenol A.
[0061] Also useful as the second comonomer (B) are cyanate ester resins and their reaction products with bismaleimides. Cyanate ester resins contain -OCN reactive moieties and are generally prepared by the reaction of cyanogen halides with diphenols or polyphenols. Suitable cyanate ester resins and methods for their preparation are disclosed in U.S. Pat. No. 4,546,131, which is incorporated herein by reference.
[0062] Prepolymers prepared by reaction of cyanate resins with epoxy or bismaleimide resins are also useful. Bismaleimide resins are commercially available as "BT triazine resins" from Mitsubishi Gas Chemical Company, Inc. Epoxy resins can be useful in the resin systems of the subject invention, as indicated above. Some such resins are described in the articles Handbook of Epoxy Resins, Lee and Neville, McGraw-Hill, (C) 1967, and Epoxy Resins Chemistry and Technology, May and Tanaka, Marcel Dekker, C. 1973. Some of the most useful epoxy resins are those derived from liquid epoxies, especially bisphenol A, bisphenol F, and p-aminophenol, because of their ability to aid in the tack of bismaleimide formulations. Generally, a small amount of epoxy resin is utilized, for example up to about 30% by weight, more preferably up to 20% by weight, and most preferably less than 10% by weight.
[0063] Toughening modifiers may also be useful as the second comonomer (B) in the practice of the subject invention. Generally, they are reactive oligomers having molecular weights between 600 and 30,000 Daltons. These modifiers may be terminal or have medial reactive groups, such as the previously mentioned allyl or propenyl phenols, and phenoxy ethers, or other groups that react with amino, maleimide, cyanate, isocyanurate, or bismaleimide. The backbones of these oligomers can be of diverse nature, for example polyarylenes, such as polyetherketones, polyetheretherketones, polysulfones, polyethersulfones, etc., as prepared in U.S. Pat. No. 4,175,175 and the article Toughening of Bis Maleimide Resins. Synthesis and Characterization of Maleimide Terminated Poly(Arylene Ether) Oligomers and Polymers, JE McGrath et al., NASA report n187-27036, Final Report Task 1-17000, the contents of both of which are incorporated herein by reference for all purposes. The backbones can also be derived from polysiloxanes, in particular poly(dicyclopentadiene)s terminated with allyl or propenylphenol or phenoxy groups. Molten Thermoplastics (C) In certain embodiments, it may be necessary to adjust the tack. With the increasing use of different types of manufacturing, adjusting the tack of the product is important. If the tack is high, hand layup of the prepreg is possible. If the tack is low, Automated Fiber Placement (AFP) and Automated Tape Layup (ATL) can be realized. The tack can be adjusted by adding a soluble thermoplastic to the resin matrix. In the case of BMI, an exemplary matrix resin, the thermoplastic soluble in the BMI or BOX matrix system can be a polyimide, such as Matrimide® 5218, or another type of polymer, such as reactive or non-reactive polysulfone, polyethersulfone, polyetherketone, polyetheretherketone, etc. The weight average molecular weight (Mw) of this additional soluble thermoplastic can be about 2000 to about 150,000 Daltons, but preferably 20,000 to about 100,000 Daltons. When the soluble thermoplastic has a Mw of 20,000 to about 100,000 Daltons, the amount of dissolvable soluble thermoplastic can be 0 to 5% by weight, excluding particles (D1) and (D2), in the thermosetting resin system. When no soluble thermoplastic is present in the resin system, the prepreg will have high tack and may be suitable for hand layup. If the soluble resin thermoplastic is less than 5% by weight, excluding particles (D1) and (D2), in the thermosetting matrix, the tack can be low enough to work well with the AFP / ATL system. For this system, low tack at room temperature and high tack when heated are preferred. If the volume percent and weight percent of particles and thermoplastic are too high, even heating may not produce enough tack, resulting in poor conditions for the AFP / ATL system. Furthermore, when the thermoplastic is present at less than 5% by weight, the prepreg will have good drapeability and handleability and will not be brittle.
[0064] Although soluble thermoplastics can be added to adjust the room temperature viscosity (related to tack) of the thermosetting matrix system, the difficulty of adding a high temperature thermosetting matrix system is the very steep viscosity curve, which results in the thermosetting resin during curing. Therefore, when the room temperature viscosity is set by the soluble thermoplastics dissolved in the thermosetting matrix, the minimum viscosity and total flow index remain too low at the curing temperature of the thermosetting resin, so that the resin flows too much during curing. This leads to uneven part thickness and hinders part manufacturing. Furthermore, the increased flow makes it difficult to control the interlayer thickness of the prepreg, and the number of particles in the interlayer may change. When the resin flow is large, specific and complicated bagging techniques are required to reduce the resin flow, which increases the complexity and time to make such bags. It has been found that by incorporating accelerators specific to high temperature resin systems together with the thermoplastics, the minimum viscosity and total flow index of the matrix system during curing can be controlled, while not affecting the room temperature viscosity. This reduction in resin flow significantly reduces the time required to manufacture CFRP parts by allowing less complicated bagging techniques. The difficulty with this approach is to select the right amount of accelerator so that it does not affect the processability of the prepreg. Accelerators / Catalysts (E) For the exemplary matrix system BMI, catalysts, also referred to herein as accelerators, are well known to those skilled in the art and include, for example, tertiary amines, metal carboxylates, such as tin(II) octoate, and especially organophosphines, organophosphine salts, complexes, and reaction products of maleimide group-containing compounds with organophosphines, such as those disclosed as useful for epoxy resin systems in U.S. Pat. No. 3,843,605, the entire contents of which are incorporated herein by reference.
[0065] In certain embodiments of the present invention, an organic phosphine is used to catalyze the BMI matrix system. In those embodiments, the amount of catalyst used is 0.01% to 0.5% by weight of the first and second comonomers (A) and (B). When the amount of catalyst is more than 0.01% and combined with the above amount of soluble thermoplastic system, the tack, minimum viscosity, and resin flow index can be adjusted to an acceptable level for both handling and proper resin flow during the curing of the thermosetting resin system. When the amount of catalyst is less than 0.5% by weight of the thermosetting resin components (A) and (B), the matrix system can be successfully processed through the prepregging system, including fiber mixing, filming, and prepregging, without excessive premature crosslinking. Viscosity of thermosetting resin composition at 40°C The viscosity of the BMI resin composition at 40°C is set to 1×10 to achieve both ease of handling and processing of the uncured FRC prepreg while maintaining the mechanical properties of the cured FRC. 3 From 3×10 4The viscosity at 40°C may be between 0.01 Pa·s. If the viscosity at 40°C is too low, the tack may be too high, which may impair handling. If the viscosity at 40°C is too high, the tack may be too low, which may cause the prepreg to be too brittle, which may result in insufficient moldability of the uncured FRC. Furthermore, the minimum viscosity at 40°C of the thermosetting resin composition should be greater than 1 Pa·s. If the minimum viscosity is too low, the resin flow may be too great, requiring special handling and molding procedures, making the material difficult to handle (e.g., excessive resin loss due to bleed-out). The viscosity of the thermosetting resin composition was measured using a dynamic viscoelasticity measuring device (ARES, TA Instruments) with parallel plates of 40 mm diameter, at a strain of 10%, a frequency of 0.5 Hz, and a plate spacing of 1 mm, while increasing the temperature from 40°C to 150°C at a rate of 2°C / min. The viscosity of the thermosetting maleimide or BMI resin composition can be adjusted and controlled as desired by the selection of the particular components used in the composition. In particular, the types and relative proportions of maleimide resins and comonomers present as components (A) and (B) can be varied as needed to adjust the overall viscosity of the thermosetting resin composition. Other Additives In addition, additional inorganic particulate materials, such as clay, may be included in the BMI resin composition as long as they do not reduce the effectiveness of the present invention. If the inorganic particulate materials are within the same size distribution as the (D1) particles, the amount of (D1) particles may be reduced to maintain the same volume distribution. An advantageous effect of certain embodiments of the present invention is that a large amount of thermoplastic (D1) particles is not required to increase the CAI. This allows for the addition of other particles that may provide other properties that may be more desirable for certain embodiments of the present invention. If the additional particles are within the same size distribution as the (D2) particles, they may be used to promote an increase in CAI along with other properties that the additional inorganic particles enhance. Although they are not as effective as certain thermoplastic particles, they can still be used to create an intermediate layer thickness that may increase the CAI and reduce the overall amount of particles required in the intermediate layer. If the particles are smaller than the size of (D1), they will mainly disperse into the layer between the fibers and will not significantly affect the CAI and the properties of certain embodiments of the present invention. Non-limiting examples of suitable inorganic particles include metal oxide particles, metal particles, and mineral particles. Inorganic particles can be used to improve one or more functions of the cured thermosetting resin composition and to impart one or more functions to the cured thermosetting resin composition. Examples of such functions include surface hardness, anti-blocking property, heat resistance, barrier property, conductivity, antistatic property, electromagnetic wave absorption, ultraviolet (UV) shielding, toughness, impact resistance, and low linear thermal expansion coefficient. Examples of other suitable inorganic materials include aluminum hydroxide, magnesium hydroxide, glass beads, glass flakes, and glass balloons.
[0066] The inorganic particles may be in the range of 1 nm to 10 μm. Any shape of inorganic particles may be used, for example, the inorganic particles may be spherical, needle-like, plate-like, balloon-like, or hollow. The inorganic particles may be used simply as a powder or as a dispersion in a solvent-like sol or colloid. Additionally, the surface of the inorganic particles may be treated with a coupling agent to improve the dispersion of the particles and the interfacial affinity with the BMI resin.
[0067] Examples of suitable particulate metal oxides include silicon oxide, titanium oxide, zirconium oxide, zinc oxide, tin oxide, indium oxide, aluminum oxide, antimony oxide, cerium oxide, magnesium oxide, iron oxide, tin-doped indium oxide (ITO), antimony-doped tin oxide, and fluorine-doped tin oxide. Examples of suitable particulate metals include gold, silver, copper, aluminum, nickel, iron, zinc, and stainless steel. Examples of suitable minerals include montmorillonite, talc, mica, boehmite, kaolin, smectite, xonotlite, vermiculite, and sericite.
[0068] Examples of other suitable carbonaceous materials include carbon black, acetylene black, ketjen black, carbon nanotubes, graphene, carbon nanofibers, carbon nanobeads, fullerenes, and the like.
[0069] In certain embodiments, the BMI resin composition may contain one or more other materials in addition to the materials described above, so long as the other materials do not reduce the effect of the present invention. Examples of other materials include mold release agents, surface treatment agents, flame retardants, antibacterial agents, leveling agents, defoamers, thixotropic agents, heat stabilizers, light stabilizers, UV absorbers, pigments, coupling agents, and metal alkoxides. Reinforced Fiber There is no particular limit or restriction on the type of reinforcing fiber that can be used, so long as it does not reduce the effect of the present invention. Examples include glass fiber, carbon fiber, and graphite fiber, such as S-glass fiber, S-1 glass fiber, S-2 glass fiber, S-3 glass fiber, E glass fiber, and L glass fiber, organic fiber, such as aramid fiber, boron fiber, metal fiber, such as alumina fiber, silicon carbide fiber, tungsten carbide fiber, and natural / bio fiber. In particular, the use of carbon fiber can provide a cured FRC material that has very high strength and stiffness and is also lightweight. Examples of suitable carbon fibers include carbon fibers manufactured by Toray having a standard elastic modulus of about 200 to 250 GPa (Torayca (registered trademark) T300, T300J, T400H, T600S, T700S, T700G), carbon fibers having an intermediate elastic modulus of about 250 to 300 GPa (Torayca (registered trademark) T800H, T800S, T1000G, M30S, M30G), or carbon fibers having a high elastic modulus of more than 300 GPa (Torayca (registered trademark) M40, M35J, M40J, M46J, M50J, M55J, M60J). Of these carbon fibers, those having a standard elastic modulus, a strength of 4.9 GPa or more, and an elongation of 2.1% or more are used in the examples.
[0070] The form and arrangement of the reinforcing fiber layer used are not particularly limited. Any of the forms and spatial arrangements of reinforcing fibers known in the art, such as long fibers in one direction, randomly oriented chopped fibers, single tow, narrow tow, woven fabric, mat, knitted fabric, and braid, may be utilized. The term "long fiber" as used herein refers to a single fiber that is substantially continuous over a length of 10 mm or more, or a fiber bundle containing the single fiber. The term "short fiber" as used herein refers to a fiber bundle containing fibers cut to a length shorter than 10 mm. In particular, in end-use applications where high specific strength and high specific modulus are desired, a form in which the reinforcing fiber bundles are arranged in one direction may be most appropriate. From the viewpoint of handling, a cloth-like (woven) form is also suitable for the present invention. Manufacturing method The FRC material of the present invention can be manufactured using methods such as prepreg lamination, resin transfer molding, resin film injection, hand lay-up, sheet molding compound, filament winding, and pultrusion, but is not particularly limited or restricted in this regard.
[0071] Resin transfer molding is a method in which a liquid thermosetting resin composition is directly impregnated into a reinforcing fiber substrate and cured. Since this method does not involve intermediate products such as prepregs, it is expected to reduce molding costs and is advantageously used in the manufacture of structural materials for spacecraft, aircraft, railroad cars, automobiles, ships, etc.
[0072] The prepreg lamination molding method is a method in which a reinforcing fiber substrate is impregnated with a thermosetting resin composition to produce a prepreg, which is then molded and / or laminated, and the resin is cured by applying heat and pressure to the molded and / or laminated prepreg to obtain an FRC material.
[0073] In the filament winding method, one to several tens of reinforcing fiber rovings are aligned in one direction, impregnated with a thermosetting resin composition, and wound around a rotating metal core (mandrel) at a specified angle under tension. After the roving wrap reaches a specified thickness, it is cured and then the metal core is removed.
[0074] The pultrusion molding method is a method in which reinforcing fibers are continuously passed through an impregnation tank filled with a liquid thermosetting resin composition to impregnate the reinforcing fibers with the thermosetting resin composition, and then the impregnated reinforcing fibers are continuously pulled out using a pulling machine, and then molded and cured through a squeeze die and a heated die. This method offers the advantage of being able to mold FRC materials continuously, and is therefore used in the manufacture of FRC materials such as fishing rods, rods, pipes, sheets, antennas, and building structures. Of these methods, the prepreg lamination molding method can be used to give the resulting FRC material excellent stiffness and strength.
[0075] The prepreg may contain a high-temperature BMI resin composition and reinforcing fibers. Such a prepreg can be obtained by impregnating a reinforcing fiber substrate with the BMI resin composition of the present invention. The impregnation method includes a wet method and a hot melt method (dry method).
[0076] The wet method is a method in which the reinforcing fibers are first immersed in a solution of the BMI resin composition produced by dissolving the BMI resin composition in a solvent, for example, methyl ethyl ketone or methanol, and then the solution is evaporated through an oven or the like to remove the solvent, and the reinforcing fibers are impregnated with the thermosetting resin composition. The hot melt method can be carried out by directly impregnating the reinforcing fibers with the BMI resin composition that has been heated to make it fluid, or by first applying the BMI resin composition to be used as a resin film to a piece of release paper or the like, and then overlaying the film on one or both sides of the reinforcing fibers configured in a planar shape, and applying heat and pressure to impregnate the reinforcing fibers with the resin. The hot melt method can result in a prepreg that is substantially free of residual solvent.
[0077] Prepreg: 40 to 500 g / m 2 The carbon fiber weight may be between 40 g / m 2 If the carbon fiber weight is less than 500 g / m, the fiber content may be insufficient and the fiber-reinforced composite (FRC) may have low strength. 2 If the resin content is more than 70wt%, the drapeability of the prepreg may be impaired, and the effect of the interlayer particles may be reduced. The prepreg may further have a resin content between 20 and 70wt%. If the resin content is less than 20wt%, impregnation may be insufficient, resulting in a large number of voids. If the resin content is more than 70wt%, the mechanical properties of the FRC may be impaired.
[0078] Prepreg lamination molding, press molding, autoclave molding, bagging molding, tape wrapping, internal pressure molding, and the like may utilize appropriate heat and pressure.
[0079] Autoclave molding is a method in which prepregs are laminated on a tool plate of a given shape, then covered with a bagging film, and cured by applying heat and pressure while removing air from the laminate. It can provide high-quality molding materials with excellent mechanical properties because of the minimal void content, as well as allowing precise control of fiber orientation. The pressure applied during the molding process can be 0.3-1.0 MPa, while the molding temperature can be in the range of 90-300°C (in one embodiment of the present invention, in the range of 180°C-220°C, or 200°C-220°C).
[0080] The wrapping tape method is a method in which prepreg is wrapped around a mandrel or some other core to form a tubular FRC material. This method can be used to manufacture golf shafts, fishing rods, and other rod-shaped products. More specifically, the method includes wrapping prepreg around a mandrel, wrapping the prepreg with a thermoplastic film wrapping tape under tension to fix the prepreg, and applying pressure thereto. After heating in an oven to cure the resin, the core is removed to obtain a tubular body. The tension used to wrap the wrapping tape can be 20-100 N. The curing temperature can be in the range of 90-300°C (in one embodiment of the present invention, 180°C-220°C, e.g., 200°C-220°C).
[0081] The internal pressure molding method is a method in which a preform obtained by winding a prepreg around a thermoplastic resin tube or some other internal pressure applicator is set in a mold, and high pressure gas is introduced into the internal pressure applicator to apply pressure and simultaneously heat the mold to mold the prepreg. This method can be used in molding objects with complex shapes, such as golf shafts, bats, and tennis or badminton rackets. The pressure applied during the molding process can be 0.1 to 2.0 MPa. The molding temperature can be between room temperature and 300°C, or in the range of 180 to 275°C (in one embodiment of the present invention, 180°C to 220°C, for example, in the range of 200°C to 220°C).
[0082] Additionally, a method for making a thermosetting resin composition is provided, the method comprising the steps of: a first comonomer (A), a second comonomer (B), Particles (D1) and comprising, consisting of, or consisting essentially of a step of merging particles (D2) and
[0083] The particles (D1) and the particles (D2) are insoluble in the first comonomer (A) and the second comonomer (B). The particles (D1) have a particle size in the range of 1 to 10 microns and a mode of 3 to 6 microns on a volume basis, and the particles (D1) comprise 3 to 12 volume % of the entire thermosetting resin composition. The particles (D2) have a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and the particles (D2) comprise 1 to 6 volume % of the entire thermosetting resin composition.
[0084] According to one embodiment, the first comonomer (A) and the second comonomer (B) may be combined first to form a monomer mixture, and then the particles (D1) and (D2) may be combined with the monomer mixture to form a thermosetting resin composition. According to another embodiment, the particles (D1) and the particles (D2) may be combined to form a particle mixture such that the particle mixture comprises, consists of, or consists essentially of two or more modes. This particle mixture comprising, consists of, or consists essentially of two or more modes may then be combined with either the first comonomer (A) or the second comonomer (B) and then with the other of the comonomer (A) or the comonomer (B) to form a thermosetting resin. According to yet another embodiment, the particle mixture comprising, consists of, or consists essentially of two or more modes may be combined with the monomer mixture to form a thermosetting resin composition. Purpose FRC materials containing the cured thermosetting resin composition obtained from the thermosetting resin composition of the present invention and reinforcing fibers are advantageously used in general industrial applications, as well as in aviation and space applications. The FRC materials can also be used in other applications, such as sports applications (e.g., golf shafts, fishing rods, tennis or badminton rackets, hockey sticks, and ski poles), and vehicle structural materials (e.g., automobiles, bicycles, ships, railroad cars, drive shafts, leaf springs, windmill blades, pressure vessels, flywheels, papermaking rollers, roofing materials, cables, and repair and reinforcement materials).
[0085] The present invention can be summarized according to the following non-limiting aspects.
[0086] Aspect 1 Reinforcement fiber and A first comonomer (A), a second comonomer (B), and Particle (D) A fiber reinforced prepreg comprising a thermosetting resin composition comprising: the particles (D) are insoluble in the first comonomer (A) and the second comonomer (B), the particles (D) comprise 4 to 18 volume % of the total thermosetting resin composition in the prepreg, and have a particle size in the range of 1 to 100 microns and at least one mode of 3 to 60 microns on a volume basis; Condition i) or ii), i.e. i) the first comonomer (A) comprises a maleimide compound and the second comonomer (B) comprises at least one of an alkenylphenol group, an alkenylphenoxy group, or a diamine group; or ii) Particles (D) include particles (D1) having a particle size in the range of 1 to 10 microns and a mode of 3 to 6 microns on a volume basis, and particles (D2) having a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and particles (D2) having a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and particles (D2) having a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and particles (D2) having a particle size in the range of 10 to 60 microns and a mode of 20 to 60 microns on a volume basis, and particles (D2) having a particle size in the range of 10 to 10 ... At least one of the above is satisfied.
[0087] Aspect 2: When at least one of conditions i) or ii) is met, a cured composite made from a fiber reinforced prepreg has a strength measured according to ASTM D7137M-17 after impact with 4.45 kJ / m: 241MPa The fiber-reinforced prepreg according to embodiment 1, having a compressive strength after impact (CAI) of or above.
[0088] Aspect 3 The prepreg includes a fiber layer and an intermediate layer, The fiber layer includes reinforcing fibers impregnated with a thermosetting resin composition, The intermediate layer contains a thermosetting resin composition and particles (D), 3. The fiber-reinforced prepreg according to any one of the preceding claims, wherein at least 90% by volume of the particles (D) remain in the intermediate layer after curing of the prepreg.
[0089] Aspect 4 The fiber-reinforced prepreg according to any one of Aspects 1 to 3, wherein the particles (D1) comprise 5 to 10% by volume of the total volume of the thermosetting resin composition.
[0090] Aspect 5 The fiber-reinforced prepreg according to any one of Aspects 1 to 4, wherein the particles (D2) comprise 2 to 4.5% of the total volume of the thermosetting resin composition.
[0091] Aspect 6 The fiber-reinforced prepreg according to any one of aspects 1 to 5, wherein the volume ratio of the particles (D1) to the particles (D2) is 90:10 to 50:50, preferably 80:20 to 40:60.
[0092] Aspect 7 The fiber-reinforced prepreg according to any one of Aspects 1 to 6, wherein the particles (D) comprise polyimide particles.
[0093] Embodiment 8 A fiber-reinforced prepreg according to any one of embodiments 1 to 7, wherein the particles (D2) have a particle size in the range of 20 to 60 microns and a mode, on a volume basis, of 20 to 50 microns.
[0094] Aspect 9: The fiber-reinforced prepreg according to any one of aspects 1 to 8, wherein the particles (D) have a glass transition temperature of 200° C. or higher, preferably 220° C. or higher.
[0095] Aspect 10 The fiber-reinforced prepreg of any one of Aspects 1 to 9, wherein the thermosetting resin composition further comprises a thermoplastic material (C) dissolved therein.
[0096] Aspect 11. The fiber-reinforced prepreg of aspect 10, wherein the thermoplastic material (C) comprises a polyimide and is present in an amount of 0.5 to 5% by mass of the entire thermosetting resin composition, excluding the weight of the particles (D1) and (D2).
[0097] Aspect 12 The fiber-reinforced prepreg of any one of aspects 1 to 11, wherein the thermosetting resin composition further comprises an accelerator in an amount sufficient to reduce a resin flow index of the thermosetting resin composition to 5 or less.
[0098] Aspect 13 The fiber-reinforced prepreg according to aspect 12, wherein the amount of the accelerator is 0.05 to 0.5% by mass, relative to components (A) and (B).
[0099]
[0036] Example 14. The fiber reinforced prepreg of example 12 or 13, wherein the accelerator comprises a phosphorus-containing accelerator.
[0100] A fiber-reinforced prepreg according to any one of the preceding claims, wherein the maleimide compound (A) comprises at least one of N,N'-4,4'-diphenylmethane-bismaleimide, N,N'-2,4-toluene-bismaleimide, N,N'-2,2,4-trimethylhexane-bismaleimide, or a mixture thereof.
[0101] Embodiment 16 The fiber-reinforced prepreg of any one of embodiments 1 to 15, wherein the maleimide compound (A) comprises a eutectic mixture of two or more bismaleimide compounds.
[0102] Embodiment 17 The fiber-reinforced prepreg of any one of embodiments 1 to 16, wherein the comonomer (B) comprises o,o'-diallyl bisphenol A.
[0103] Aspect 18 A copolymer comprising a first comonomer (A), and a second comonomer (B), A thermosetting resin composition comprising particles (D), A thermosetting resin composition, wherein the particles (D) are insoluble in the first comonomer (A) and the second comonomer (B), the particles (D) comprise 4 to 18 volume % of the entire thermosetting resin composition in a prepreg, and have a particle size in the range of 1 to 100 microns and at least one mode of 3 to 60 microns on a volume basis, Condition i) or ii), i.e. i) the first comonomer (A) comprises a maleimide compound and the second comonomer (B) comprises at least one of an alkenylphenol group, an alkenylphenoxy group, or a diamine group; or ii) Particles (D) include particles (D1) having a particle size in the range of 1 to 10 microns and a mode of 3 to 6 microns on a volume basis, which particles (D1) comprise 3 to 12 volume % of the entire thermosetting resin composition, and particles (D2) having a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, which particles (D2) comprise 1 to 6 volume % of the entire thermosetting resin composition. At least one of the above requirements is satisfied.
[0104] Aspect 19: The thermosetting resin composition according to aspect 18, wherein the volume ratio of the particles (D1) to the particles (D2) is 90:10 to 50:50.
[0105] Example 20. The thermosetting resin composition of example 18 or example 19, wherein the particles (D1) comprise polyimide particles.
[0106] Aspect 21 The thermosetting resin composition according to any one of Aspects 18 to 20, wherein the particles (D2) have a particle size in the range of 20 to 60 microns and a mode, on a volume basis, of 20 to 40 microns.
[0107] Aspect 22 The thermosetting resin composition according to any one of Aspects 18 to 21, wherein the particles (D1) have a glass transition temperature of 200° C. to 400° C., preferably 220° C. to 400° C., and more preferably 220° C. or higher.
[0108] Aspect 23 The thermosetting resin composition of any one of Aspects 18-22, further comprising a thermoplastic material (C) dissolved therein.
[0109]
[0041] Aspect 24. The thermosetting resin composition of aspect 23, wherein the thermoplastic material (C) comprises a polyimide.
[0110] Aspect 25 The thermosetting resin composition of any one of Aspects 18-24, further comprising an accelerator in an amount sufficient to reduce a resin flow index of the thermosetting resin to 5 or less.
[0111] Aspect 26 The thermosetting resin composition according to aspect 25, wherein the amount of the accelerator is 0.05 to 0.5% by weight, based on the components (A) and (B).
[0112]
[0046] Example 27. The thermosetting resin composition of example 25 or 26, wherein the accelerator comprises a phosphorus-containing accelerator.
[0113] Aspect 28. The thermosetting resin composition of any one of Aspects 18 to 27, wherein the maleimide compound (A) comprises at least one of N,N'-4,4'-diphenylmethane-bismaleimide, N,N'-2,4-toluene-bismaleimide, N,N'-2,2,4-trimethylhexane-bismaleimide, or a mixture thereof.
[0114] Aspect 29 The thermosetting resin composition of any one of Aspects 18 to 28, wherein the second comonomer (B) comprises o,o'-diallyl bisphenol A.
[0115] Aspect 30 A copolymer comprising a first comonomer (A), a second comonomer (B), Particle (D1), A method for making a thermosetting resin composition, comprising combining particles (D2) with the A method for producing a thermosetting resin composition, wherein particles (D1) and particles (D2) are insoluble in a first comonomer (A) and a second comonomer (B), the particles (D1) have a particle size in the range of 1 to 10 microns and a mode of 3 to 6 microns on a volume basis, and the particles (D1) comprise 3 to 12 volume% of the entire thermosetting resin composition, and the particles (D2) have a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and the particles (D2) comprise 1 to 6 volume% of the entire thermosetting resin composition.
[0116] Example 31. The method of example 30, wherein the first comonomer (A) and the second comonomer (B) are combined to form a monomer mixture, and then the particles (D1) and (D2) are combined with the monomer mixture to form the thermosetting resin composition.
[0117] Example 32. The method of example 31, wherein the particles (D1) and the particles (D2) are combined to form a particle mixture comprising two or more modes, and then the particle mixture is combined with a monomer mixture to form the thermosetting resin composition.
[0118] Embodiment 33 The method of embodiment 30, wherein the particles (D1) and the particles (D2) are combined to form a particle mixture comprising two or more modes.
[0119]
[0041] Example 34. The method of example 33, wherein the particle mixture is combined with either a first comonomer (A) or a second comonomer (B) and then combined with the other of comonomer (A) or comonomer (B) to form a thermoset.
[0120] Within this specification, the embodiments have been described in a manner that enables a clear and concise specification to be written, but it is intended and will be understood that the embodiments can be variously combined or separated without departing from the invention, for example, it will be understood that all preferred features described herein are applicable to all aspects of the invention described herein.
[0121] In some embodiments, the invention herein may be construed to exclude any element or process step that does not materially affect the basic and novel characteristics of the composition or process. Further, in some embodiments, the invention may be construed to exclude any element or process step not specified herein.
[0122] Although the invention is illustrated and described herein with reference to specific embodiments, it is not intended that the invention be limited to the details shown, but rather that various changes can be made in the details within the scope and range of equivalents of the claims without departing from the invention. Working Example The embodiments of the present invention will now be described in more detail with reference to examples. Measurements of various properties were performed using the methods described below. These properties were measured under environmental conditions of 23°C temperature and 50% relative humidity unless otherwise noted. Prepregs were then made from the exemplary resins using a hot melt prepreg method. The components used in the examples and comparative examples, as shown in Table 1 (Examples) and Table 2 (Comparative Examples), are as follows:
[0123] Reinforcing Fiber In the examples and comparative examples, the following carbon fiber "Torayca (registered trademark)" fiber manufactured by Toray Industries, Inc. was used.
[0124] Component A, maleimide compounds Compimide® 353A (manufactured by Evonik Industries AG), N,N'-4,4'-diphenylmethane-bismaleimide, N,N'-2,4-toluene-bismaleimide, and N,N'-2,2,4-trimethylhexane-bismaleimide Component B, comonomer Compimide® TM124 (Evonik Industries AG), o,o'-diallyl bisphenol A Component C, Thermoplastic Matrimid® 9725 Particles (D1) Polyimide P84® NT SF from Evonik Industries (nominal size 1-10 microns) Particles (D2) Polyimide P84® NTF manufactured by Evonik Industries (nominal size 10-100 microns) The subject invention used bismaleimide resins in the examples, but should not be limited to bismaleimides only, other high temperature materials such as benzoxazine (BOX) and high temperature epoxies having a Tg above 200° C. are also contemplated as embodiments of the invention. Measurement of glass transition temperature of cured resin (Tg by DMA Torsion) The resin composition was discharged into a mold cavity set to a thickness of 2 mm using a metal spacer having a thickness of 2 mm. Next, this resin composition was heat-treated and cured in a convection oven under the above-mentioned curing conditions 1 and 2 to obtain a 2 mm-thick curable resin plate. A test piece having a length of 50 mm and a width of 12.7 mm was cut out from the above-mentioned plate, and Tg was measured by heating at a rate of 5°C / min to a temperature of 40°C to 350°C in accordance with SACMA Recommended Methods (SRM) 18R-94 (glass transition temperature measurement) of the Suppliers of Advanced Composite Materials (SACMA). Tg was determined by determining the intersection of the tangent of the glass region and the tangent of the transition region from the glass region to the rubber region on the heat storage elastic modulus curve, and the temperature at the intersection is regarded as the glass transition temperature, and is generally called the G' onset Tg. Compression after impact (CAI) measurements CFRP panels were prepared with the following layup configuration [+45° / 0° / -45° / 90°] 3S 24ply according to the method described in "Prepreg Curing". After curing, the CFRP panels were 10cm × 15cm The test coupons were tested according to ASTM standard ASTM D 7137M-17. The compressive strength of each coupon was measured using a thickness of 2.5cm After impacting the specimen with 1000 in-lb (4.45 kJ / m) per impact, the specimen was tested according to ASTM standard ASTM D 7137M-17. Fiber Weight The resin areal weight (RAW) was determined by taking a film of resin before prepregging, cutting out a 100 x 100 mm square sample, scraping off the resin on the square, and measuring the weight of the resin. The resin areal weight was calculated by dividing twice this weight by the area of the square sample. The fiber areal weight (FAW) was measured after prepregging using the same method, cutting out a 100 x 100 mm square sample, measuring the weight of the prepreg, and subtracting the RAW from this value. Resin content in prepreg Resin content (RC) is the mass% of resin in the prepreg, hereinafter RC=RAW / [(RAW+FAW)] It was calculated as follows. Viscosity of uncured resin Uncured resin specimens were placed in a 40 mm diameter parallel plate rheometer (ARES, TA Instruments) preheated to 40° C. with a gap of 0.6 mm. A torsional displacement of 10 rad / s was applied. The temperature was increased at 2° C. / min to determine the minimum viscosity of the resin. Particle Size Measurement Particles were measured using static light scattering and Mie theory (assuming spherical particles similar to the wavelength of the incident light) and the results were analyzed using the following method and equipment. The equipment used was a Mastersizer 2000 using a Scirocco 2000 cell cassette for dry method measurements. The Mastersizer 2000 was run with the following settings: Dispersion medium = air Absorption value = 0 Refractive index = 1.50 Obscuration setting = 1-12% Dispersion conditions = 0.35bar at 65% Gate gap width = approx. 0.125'' was set to. The measurement time for each sample was set to 6 seconds.
[0125] As is known in the art, the results are reported as frequency distribution curves, i.e., diameter frequency is plotted on the y-axis versus particle size (diameter) on the x-axis. The results can be analyzed to determine the range and mode of each peak so obtained.
[0126] The measurements reported are particle size (diameter) per volume percentage (%) of total particles. Particle size measurement (optical microscope) Another method available for determining particle size distribution is optical microscopy. This method for determining the volume percent of particles in the interlayer and within the layers is as follows: The cured samples were sectioned, cross cut, and polished using an abrasive wheel to a 3 micron finish or better. This was accomplished by using an automated polishing machine such as the Tegramin machine available from Struers. Once polished, the volume distribution of particle size was measured using a microscope at 300x or higher and Zeiss Zen software (with particle size and counting modules). Once the size was determined, a particle size distribution diagram was created. If the particles are difficult to resolve, a fluorescent light source with appropriate filters may be used to increase the contrast between the particles and the matrix resin. Resin flow index The resin flow index is calculated from the viscosity of the uncured resin. The viscosity of the uncured resin is measured as described above. After measuring the viscosity of the uncured resin from 40°C to 140°C, the flow index was calculated by the following formula.
[0127]
number
[0128] The tack was considered to be "high tack," "medium tack," and "low tack" in comparison to the 3900-2B / T800S standard prepreg. Volume percentage of particles remaining in the interlayer after curing The method for determining the volume % of particles in and within the interlayer is as follows: The cured samples were sectioned, cross cut, and polished using an abrasive wheel to a 3 micron finish or better. This was accomplished by using an automated polishing machine such as the Tegramin manufactured by Struers. Once polished, the surface was analyzed using a microscope at 300x magnification or greater using Zeiss Zen software with the particle size and counting module to determine the volume % of particles in and within the interlayer. If the particles are difficult to resolve, a fluorescent light source with appropriate filters may be used to improve the contrast between the particles and the matrix resin. Production of thermosetting resin composition According to the number of parts, a predetermined amount of the second comonomer (B) and the thermoplastic resin (C) were mixed and heated at 120°C for 1 hour to dissolve the thermoplastic resin. Furthermore, the bismaleimide compound as the first comonomer (A) was melted separately at 140°C. The mixture and the bismaleimide compound as the first comonomer (A) were mixed after lowering the temperature to 100°C, and an accelerator was added at 60°C, and then kneaded to prepare a high heat-resistant thermosetting resin composition. Tables 1 to 4 summarize the compositions of various exemplary resin compositions and the properties of the resulting cured resins. Prepreg manufacturing A prepreg containing carbon fiber impregnated with the specified resin composition was prepared. The resin composition prepared as shown in the table was applied to a release paper with a knife coater to obtain a resin mass per unit area of 52 g / m. 2 Two resin films were produced. The carbon fiber structure was arranged in one direction (mass per unit area was 190 g / m 2 The two resin films prepared above were superimposed on both sides of the carbon fiber sheet (D1), and heat and pressure were applied at a temperature of 100°C and a pressure of 1 atm using a heated roll to impregnate the carbon fiber with the thermosetting resin composition and the particles (D1) and (D2), thereby obtaining a prepreg. In Examples 1 to 8, 10 to 13, and Comparative Examples 1 and 4 to 11, Torayca® fiber T1100G-F1E was used to manufacture the prepreg. In Comparative Examples 2 and 3, and Example 9, Torayca® fiber T1100G-51E was used to manufacture the prepreg. Prepreg curing The prepreg obtained above is cut and laminated, subjected to vacuum bag molding, and cured in a vacuum-exposed autoclave under the following curing conditions 1 at a pressure of 1000 MPa. 0.14MPa During the initial temperature ramp, 0.59MPa A voltage was applied and maintained throughout the cure cycle. The prepreg was post-cured in a convection oven using cure condition 2 below. Curing conditions 1 1. Heat from room temperature to 143℃ at a rate of 1.7℃ / min. 2. Hold at 143°C for 2 hours. 3. Heat from 143℃ to 190℃ at a rate of 1.7℃ / min. 4. Hold at 190℃ for 2 hours. 5. Reduce the temperature from 190°C to 30°C at a rate of 2°C / min. Curing conditions 2 1. Heat from room temperature to 227℃ at a rate of 1.7℃ / min. 2. Hold at 227℃ for 4 hours. 3. Reduce the temperature from 227°C to 30°C at a rate of 2°C / min.
[0129] The experimental results are shown in Tables 1 and 2 for the examples and in Tables 3 and 4 for the comparative examples. Thermosetting resin components (A) and (B) are provided in weight percent based on the sum of components (A), (B), (C), (D1), (D2) and (E). Component (C) is provided as weight percent based on the sum of components (A), (B), (C) and (E) (i.e., excluding the weight of particles (D1) and (D2)). Component (E) is provided as weight percent based on the weight of components (A) and (B). Particles (D1) and (D2) are given as volume percent based on the total volume of thermosetting resin components (A), (B), (C), (D1), (D2) and (E).
[0130] [Table 1]
[0131] [Table 2]
[0132] [Table 3]
[0133] [Table 4] As can be seen from the above examples, Examples 1 and 2 use IM30K glass bubbles with an average particle size of 20 microns for the (D2) particles and P84 SF particles for the (D1) particles. The results demonstrate that a higher relative amount of (D2) particles in combination with (D1) particles shows an increase in CAI compared to Comparative Examples 3 and 4, which used only IM30K glass bubbles (D2) as the toughening particles. Surprisingly, a relatively small amount of small particles (D1) was required to achieve a large change in CAI value compared to samples that did not contain any (D1) particles.
[0134] Examples 3-13 use P84 particles in both (D1) and (D2), but use different ratios and amounts of (D1) and (D2) particles. As can be seen from the CAI values, all 290MPa Example 13 demonstrates that the combination of (D1) and (D2) particles, without thermoplastics or accelerators, toughens even high flow resin systems that are traditionally difficult to toughen.
[0135] Example 12, although slightly away from the 50:50 ratio, still exhibits a high CAI, although not as high as the other examples.
[0136] Comparative Examples 3-7 and 10 or 11 use a single particle for toughening. Notably, these examples have lower CAI values despite incorporating similar loadings as the examples in which two particle size distributions are used.
[0137] Comparative Examples 1 and 2 do not contain particles and show the CAI of this resin system without the addition of particles.
[0138] Comparative Example 5 shows good CAI, but at the expense of a very high amount of (D1) P84 SF particles. This large amount of (D1) particles made the sample very difficult to process, and higher than normal temperatures were required to properly mix and deposit the prepreg. The higher temperatures reduced processing time due to increased reactivity at these temperatures. Additionally, the resulting prepreg had little to no tack. This material could still be fabricated into cured CFRP parts, but would not be practical as a commercial product.
[0139] Because larger particles are believed to produce better crack arrest and smaller particles allow for better packing, it was surprising to find that only a small amount of larger particles (D2) used with a majority of smaller particles (D1) resulted in better fracture toughness than either the use of only (D2) particles or the use of a large amount of larger particles (D2), despite predictions to the contrary based on fracture mechanics teachings. Moreover, it was even more surprising that such high CAI results were achieved with a bimodal distribution of particle sizes compared to the use of a single distribution of either only large particles such as (D2) particles or only small particles such as (D1) particles.
Claims
1. Reinforced fibers, A first comonomer (A), A second comonomer (B), and Particle (D) A fiber reinforced prepreg comprising a thermosetting resin composition comprising: the particles (D) are insoluble in the first comonomer (A) and the second comonomer (B), the particles (D) comprise 4 to 18 volume % of the total thermosetting resin composition in the prepreg, and have a particle size in the range of 1 to 100 microns and at least one mode of 3 to 60 microns on a volume basis; Conditions i) and ii), i.e. i) the first comonomer (A) comprises a maleimide compound and the second comonomer (B) comprises at least one of an alkenylphenol group, an alkenylphenoxy group, or a diamine group; and ii) The particles (D) include particles (D1) having a particle size in the range of 1 to 10 microns and a mode of 3 to 6 microns on a volume basis, and particles (D2) having a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and particles (D2) having a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and particles (D2) having a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and particles (D2) having a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and particles (D2) having a particle size in the range of 10 to 60 microns and a mode of 20 to 60 microns on a volume basis, and particles (D2) having a particle size in the range of 10 to 10 ... That is met, fiber reinforced prepreg.
2. 2. The fiber reinforced prepreg according to claim 1, wherein a cured composite made from the fiber reinforced prepreg has a compressive strength after impact (CAI) of 241 MPa or more, measured according to ASTM standard ASTM D7137M-17, after impact with 4.45 kJ / m, when conditions i) and ii) are met.
3. The prepreg includes a fiber layer and an intermediate layer, The fiber layer includes the reinforcing fiber impregnated with the thermosetting resin composition, the intermediate layer contains the thermosetting resin composition and the particles (D), 3. The fiber-reinforced prepreg according to claim 1 or 2, wherein at least 90% by volume of the particles (D) remain in the intermediate layer after curing of the prepreg.
4. The fiber-reinforced prepreg according to any one of claims 1 to 3, wherein the particles (D1) comprise 5 to 10% by volume of the total volume of the thermosetting resin composition.
5. The fiber-reinforced prepreg according to any one of claims 1 to 4, wherein the particles (D2) comprise 2 to 4.5% of the total volume of the thermosetting resin composition.
6. The fiber-reinforced prepreg according to any one of claims 1 to 5, wherein the volume ratio of the particles (D1) to the particles (D2) is 90:10 to 50:
50.
7. A fiber-reinforced prepreg described in any one of claims 1 to 5, wherein the volume ratio of the particles (D1) to the particles (D2) is 80:20 to 40:
60.
8. The fiber-reinforced prepreg according to any one of claims 1 to 7, wherein the particles (D) include polyimide particles.
9. The fiber-reinforced prepreg according to any one of claims 1 to 8, wherein the particles (D2) have a particle size in the range of 20 to 60 microns and a mode, on a volume basis, of 20 to 50 microns.
10. The fiber-reinforced prepreg according to any one of claims 1 to 9, wherein the particles (D) have a glass transition temperature of 200 ° C. or higher.
11. A fiber-reinforced prepreg described in any one of claims 1 to 9, wherein the particles (D) have a glass transition temperature of 220°C or higher.
12. The fiber reinforced prepreg according to any one of claims 1 to 11, wherein the thermosetting resin composition further comprises a thermoplastic material (C) dissolved therein.
13. The fiber-reinforced prepreg according to claim 12, wherein the thermoplastic material (C) comprises a polyimide and is present in an amount of 0.5 to 5 mass% of the total thermosetting resin composition excluding the weight of the particles (D1) and (D2).
14. The fiber-reinforced prepreg according to any one of claims 1 to 13, wherein the thermosetting resin composition further comprises an accelerator in an amount sufficient to reduce a resin flow index of the thermosetting resin composition to 5 or less.
15. The fiber-reinforced prepreg according to claim 14, wherein the amount of the accelerator is 0.05 to 0.5% by weight relative to components (A) and (B).
16. 16. The fiber reinforced prepreg of claim 14 or 15, wherein the accelerator comprises a phosphorus-containing accelerator.
17. The fiber-reinforced prepreg according to any one of claims 1 to 16, wherein the maleimide compound (A) comprises at least one of N,N'-4,4'-diphenylmethane-bismaleimide, N,N'-2,4-toluene-bismaleimide, N,N'-2,2,4-trimethylhexane-bismaleimide, or a mixture thereof.
18. The fiber-reinforced prepreg according to any one of claims 1 to 17, wherein the maleimide compound (A) comprises a eutectic mixture of two or more bismaleimide compounds.
19. The fiber-reinforced prepreg according to any one of claims 1 to 18, wherein the comonomer (B) comprises o,o'-diallyl bisphenol A.
20. A first comonomer (A), A second comonomer (B), A thermosetting resin composition comprising particles (D), the particles (D) are insoluble in the first comonomer (A) and the second comonomer (B), the particles (D) comprise 4 to 18 volume % of the total thermosetting resin composition in the prepreg, and have a particle size in the range of 1 to 100 microns and at least one mode of 3 to 60 microns on a volume basis; Conditions i) and ii), i.e. i) the first comonomer (A) comprises a maleimide compound, and the second comonomer (B) comprises at least one of an alkenylphenol group, an alkenylphenoxy group, or a diamine group; and ii) The particles (D) include particles (D1) having a particle size in the range of 1 to 10 microns and a mode of 3 to 6 microns on a volume basis, which particles (D1) comprise 3 to 12 volume % of the entire thermosetting resin composition, and particles (D2) having a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, which particles (D2) comprise 1 to 6 volume % of the entire thermosetting resin composition. The thermosetting resin composition satisfies the above requirements.
21. The thermosetting resin composition according to claim 20, wherein the volume ratio of the particles (D1) to the particles (D2) is 90:10 to 50:
50.
22. The thermosetting resin composition according to claim 20 or 21, wherein the particles (D1) comprise polyimide particles.
23. The thermosetting resin composition according to any one of claims 20 to 22, wherein the particles (D2) have a particle size in the range of 20 to 60 microns and a mode of 20 to 40 microns on a volume basis.
24. The thermosetting resin composition according to any one of claims 20 to 22, wherein the particles (D1) have a glass transition temperature of 200 ° C. to 400 ° C.
25. A thermosetting resin composition described in any of claims 20 to 22, wherein the particles (D1) have a glass transition temperature of 220°C to 400°C.
26. The thermosetting resin composition described in any one of claims 20 to 22, wherein the particles (D1) have a glass transition temperature of 220°C or higher.
27. The thermosetting resin composition of any one of claims 22 to 26, further comprising a thermoplastic material (C) dissolved therein.
28. 28. The thermosetting resin composition of claim 27, wherein the thermoplastic material (C) comprises a polyimide.
29. The thermosetting resin composition according to any one of claims 22 to 28, further comprising an accelerator in an amount sufficient to reduce the resin flow index of the thermosetting resin to 5 or less.
30. 30. The thermosetting resin composition according to claim 29, wherein the amount of the accelerator is 0.05 to 0.5% by weight based on components (A) and (B).
31. 31. The thermosetting resin composition of claim 29 or 30, wherein the accelerator comprises a phosphorus-containing accelerator.
32. The thermosetting resin composition according to any one of claims 22 to 31, wherein the maleimide compound (A) comprises at least one of N,N'-4,4'-diphenylmethane-bismaleimide, N,N'-2,4-toluene-bismaleimide, N,N'-2,2,4-trimethylhexane-bismaleimide, or a mixture thereof.
33. The thermosetting resin composition according to any one of claims 22 to 32, wherein the second comonomer (B) comprises o,o'-diallyl bisphenol A.
34. A first comonomer (A), A second comonomer (B), Particles (D1), A method for making a thermosetting resin composition, comprising combining particles (D1) and particles (D2), A method for preparing a thermosetting resin composition, wherein the particles (D1) and the particles (D2) are insoluble in the first comonomer (A) and the second comonomer (B), the particles (D1) have a particle size in the range of 1 to 10 microns and a mode of 3 to 6 microns on a volume basis, and the particles (D1) comprise 3 to 12 volume % of the total thermosetting resin composition, and the particles (D2) have a particle size in the range of 10 to 100 microns and a mode of 20 to 60 microns on a volume basis, and the particles (D2) comprise 1 to 6 volume % of the total thermosetting resin composition.
35. 35. The method of claim 34, wherein the first comonomer (A) and the second comonomer (B) are combined to form a monomer mixture, and then the particles (D1) and (D2) are combined with the monomer mixture to form the thermosetting resin composition.
36. 36. The method of claim 35, further comprising combining the particles (D1) and the particles (D2) to form a particle mixture containing two or more modes, and then combining the particle mixture with the monomer mixture to form the thermosetting resin composition.
37. 35. The method of claim 34, wherein the particles (D1) and the particles (D2) are combined to form a particle mixture comprising two or more modes.
38. 38. The method of claim 37, wherein the particle mixture is combined with either the first comonomer (A) or the second comonomer (B) and then combined with the other of the comonomer (A) or the comonomer (B) to form the thermoset resin.
Citation Information
Patent Citations
Reinforced thermosetting structural material
JP1991197559A
Fiber-reinforced prepreg and composite material obtained from it
JP2007254676A
Thermosetting bismaleimide-based resin composition, prepreg using the resin composition, and method for producing the same
JP2014114369A
Prepreg and fiber-reinforced composite material
WO2013015299A1
Prepreg and fiber-reinforced composite material
WO2018174250A1